2021
DOI: 10.3389/fnbot.2021.633248
|View full text |Cite
|
Sign up to set email alerts
|

A Socially Assistive Robot for Long-Term Cardiac Rehabilitation in the Real World

Abstract: What are the benefits of using a socially assistive robot for long-term cardiac rehabilitation? To answer this question we designed and conducted a real-world long-term study, in collaboration with medical specialists, at the Fundación Cardioinfantil-Instituto de Cardiología clinic (Bogotá, Colombia) lasting 2.5 years. The study took place within the context of the outpatient phase of patients' cardiac rehabilitation programme and aimed to compare the patients' progress and adherence in the conventional cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 72 publications
2
33
0
Order By: Relevance
“…Finally, it is significant to emphasize that social interaction has been shown to have a positive impact on general mental and physical well-being in physical exercise therapy [ 79 , 80 ]. Therefore, the use of these artificial intelligence systems has a great potential in physical rehabilitation scenarios application through the use of socially assistive robots (SAR) [ 81 , 82 , 83 ]. SAR is a system that employs interaction strategies, including the use of speech, facial expressions, and communicative gestures, to assist according to a specific healthcare environment [ 80 ].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is significant to emphasize that social interaction has been shown to have a positive impact on general mental and physical well-being in physical exercise therapy [ 79 , 80 ]. Therefore, the use of these artificial intelligence systems has a great potential in physical rehabilitation scenarios application through the use of socially assistive robots (SAR) [ 81 , 82 , 83 ]. SAR is a system that employs interaction strategies, including the use of speech, facial expressions, and communicative gestures, to assist according to a specific healthcare environment [ 80 ].…”
Section: Related Workmentioning
confidence: 99%
“…SAR is a system that employs interaction strategies, including the use of speech, facial expressions, and communicative gestures, to assist according to a specific healthcare environment [ 80 ]. Several studies have shown that SAR systems improve (i) the ability to influence the patient’s intrinsic motivation to perform the task and (ii) the ability to personalize the social interaction to maintain user engagement in the task through permanent patient monitoring and feedback [ 79 , 81 , 82 , 83 , 84 , 85 , 86 ]. Therefore, with the support of the machine learning models, this technology has been used to provide better service and improve patient’s experience and treatment outcomes [ 81 , 83 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These multi-tasking processes can affect the quality of the assistance provided by the clinicians towards the patients, since there are several variables that must be measured during therapy, such as heart rate, posture and space-time parameters of gait [8,9]. Moreover, PR has to be a comprehensive strategy that includes social and psychological approaches to increase patients' engagement and motivation [10]. Motivation is a fundamental tool in establishing adherence to a therapy regimen or task scenario and promoting behavior change [11].…”
Section: Introductionmentioning
confidence: 99%
“…Casas et al [10,23] present a perception study applied to the clinicians and patients who participate in the Cardiac Rehabilitation (CR) service. A questionnaire based on the unified theory of acceptance and the use of technology (UTAUT) was implemented.…”
Section: Introductionmentioning
confidence: 99%